Small ruminant production in the humid tropical zone of southern Nigeria - Matthewman, R.W. (Springer, 1980)
Presents the results of a study on the village sheep and goat production systems in the humid tropical zone of south-west Nigeria. Herd and flock population dynamics was outlined with discussions on: the importance of goat and sheep production in the area; suggestions for methods of improvement and the problems of livestock production in areas of endemic trypanosomiasis. It was concluded that where cattle were excluded due to trypanosomiasis and where human population pressure was high, goats and sheep had continuing and increasing role to play in providing meat for the expanding human population.